Molecular strain typing of the yaws pathogen, Treponema pallidum subspecies pertenue - Katz, S.S.; Chi, K.H.; Nachamkin, E.; Danavall, D.; Taleo, F.; Addo, K.K.; Kool, J.L.; Ampofo, W.; Simpson, S.V.; Ye, T.et.al. (PLoS ONE, 2018)
Yaws is a neglected tropical disease caused by the bacterium Treponema pallidum subspecies pertenue. The disease primarily affects children under 15 years of age living in low socioeconomic conditions in tropical areas. As a result of a renewed focus on the disease owing to a recent eradication effort initiated by the World Health Organization, we have evaluated a typing method, adapted from and based on the enhanced Centers for Disease Control and Prevention typing method for T. pallidum subsp. pallidum, for possible use in epidemiological studies. Thirty DNA samples from yaws cases in Vanuatu and Ghana, 11 DNA samples extracted from laboratory strains, and 3 published genomic sequences were fully typed by PCR/RFLP analysis of the tpr E, G, and J genes and by determining the number of 60-bp repeats within the arp gene. Subtyping was performed by sequencing a homonucleotide “G” tandem repeat immediately upstream of the rpsA gene and an 84-bp region of tp0548. A total of 22 complete strain types were identified; two strain types in clinical samples from Vanuatu (5q11/ak and 5q12/ak), nine strain types in clinical samples from Ghana (3q12/ah, 4r12/ah, 4q10/j, 4q11/ah, 4q12/ah, 4q12/v, 4q13/ah, 6q10/aj, and 9q10/ai), and twelve strain types in laboratory strains and published genomes (2q11/ae, 3r12/ad, 4q11/ad, 4q12/ad, 4q12/ag, 4q12/v, 5r12/ad, 6r12/x, 6q11/af, 10q9/r, 10q12/r, and 12r12/w). The tpr RFLP patterns and arp repeat sizes were subsequently verified by sequencing analysis of the respective PCR amplicons. This study demonstrates that the typing method for subsp. pallidum can be applied to subsp. pertenue strains and should prove useful for molecular epidemiological studies on yaws.